Interpretation of ileal biopsies - Prasenjit Das; Gaurav P. S. Gahlot; Ritu Mehta; Siddhartha Datta Gupta (Wolters Kluwer Medknow Publications, 2015)
The ileum is one of the most common sites of intestine to undergo endoscopic biopsy. However, even with the experienced histopathologists, a definite diagnosis can be achieved only in 18% cases. Lack of knowledge about proper tissue handling, tissue orientation, overlapping histological findings, and lack of a standard algorithm based approach results in this low diagnostic yield. In this review article, we have tried to discuss these aspects and give a clear picture how to approach the ileal lesions. It would help the surgical pathologists in effectively interpreting the lesions and to identify the common pitfalls.